2012
DOI: 10.1002/ps.3291
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant activity of Jatropha gossypifolia and Melia azedarach senescent leaf extracts on Spodoptera frugiperda (Lepidoptera: Noctuidae) and their potential use as synergists

Abstract: Both J. gossypifolia and M. azedarach SLEs are antifeedants to armyworm larvae when present in the food, and also have a synergistic effect with cypermethrin in topical assays. Although the synergistic effect is less than with piperonyl butoxide, both SLEs have some inhibitor activity against detoxification enzymes and acetylcholinesterase. Thus J. gossypifolia and M. azedarach SLEs may be considered as ecofriendly approaches for the control of S. frugiperda in order to reduce cypermethrin usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 31 publications
3
49
0
1
Order By: Relevance
“…Bullangpoti et al [49] isolated ricinine from the ethyl acetate extract from senescent leaves, the main compound responsible for the toxicity of the crude extract in Spodoptera exigua larvae, thus demonstrating that it could be an alternative choice to chemical insecticides. In another study, Bullangpoti et al [132] showed that the ethanol extract of J. gossypiifolia in association with the ethanol extract of Melia azedarach was toxic and inhibited some enzymes from Spodoptera frugiperda larvae, demonstrating once more the potentiality of the species as insecticide agent. Calatayud et al [56] showed the presence of proteins of about 100 kDa with toxic activity upon Phenacoccus herreni, another type of insect.…”
Section: Other Actions and Biotechnological Applicationsmentioning
confidence: 99%
“…Bullangpoti et al [49] isolated ricinine from the ethyl acetate extract from senescent leaves, the main compound responsible for the toxicity of the crude extract in Spodoptera exigua larvae, thus demonstrating that it could be an alternative choice to chemical insecticides. In another study, Bullangpoti et al [132] showed that the ethanol extract of J. gossypiifolia in association with the ethanol extract of Melia azedarach was toxic and inhibited some enzymes from Spodoptera frugiperda larvae, demonstrating once more the potentiality of the species as insecticide agent. Calatayud et al [56] showed the presence of proteins of about 100 kDa with toxic activity upon Phenacoccus herreni, another type of insect.…”
Section: Other Actions and Biotechnological Applicationsmentioning
confidence: 99%
“…Similar components are present in M. azedarach (Kraus, 1986; Breuer et al, 2003). Bullangpoti et al (2012) proved that in vitro experiments with M. azedarach senescent leaf extracts inhibit esterases and P450 enzymes. Also Feng et al (1995) clearly pointed out the extract of M. toosendan inhibit midgut esterases of S. litura …”
Section: Effect Of Meliaceae Secondary Metabolites On Nadph Cytochrommentioning
confidence: 99%
“…Many effects have been attributed to M. azedarach, such as repellence, antifeedant effects, developmental delay and halting of ecdysis, reduction of fertility and fecundity, behavioral and physiological changes leading to possible mortality (Defagó et al, 2006;Nathan, 2006;Bullangpoti et al, 2012).…”
Section: Introductionmentioning
confidence: 99%